Budaya Inovasi : Upaya Membangun Organisasi Publik Yang Agile - Suryani, Eny; Hasanah, Nesia Nisatul; Fauzi, Fadhil Miftah; Suhaedi, Edi; Cadith, Juliannes (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
The ever-changing world conditions demand that public organizations can survive, where a culture of innovation can be used as a basis in facing global competition. An agile governance approach in public organizations is needed to deal with this situation. The purpose of this research is to influence the factors that influence the culture of innovation in order to build an agile public organization. This research method is a literature study with research journals related to the culture of innovation in public organizations. The results of the study there are 3 factors that affect the culture of innovation, namely: first is the commitment of the leadership in order to encourage change, Second is a flexible organizational structure that can support a culture of innovation and creativity of personnel. Third is the approach/strategy used to support the creation of a culture of innovation in public organizations. Agile public organizations allow public organizations to quickly adjust and ensure better public services where a culture of innovation is the foundation for achieving this goal.